Tanggung Jawab Pengangkut Atas Tindakan Pemungutan Tarif Yang Tidak Sesuai Aturan - Hapsa Marasabessy; Merry Tjoanda; Sarah Selfina Kuahaty (Faculty of Law Universitas Pattimura, 2023)
Public transportation plays an important role in economic development, to achieve sustainability public transportation requires serious handling. Transportation is said to be important because it is related to the distribution of goods, services and labor, and is the core of urban economic movement. The carrier or owner of public transportation is responsible for the safety of the goods being transported, in accordance with the provisions in Article 438 paragraph (3) of the Commercial Code and the provisions for determining tariffs by the city government in Ambon Mayor Decree Number 347 of 2022 concerning Adjustments to Road Transport Tariffs for Passengers Economy Class in Ambon City. Even though the carrier's responsibilities and provisions related to fare prices have been determined, drivers as carriers are still not responsible for setting fare prices to passengers, in general there is no classification, which should be in accordance with the provisions set by the government. The method used in this research is normative juridical. And uses a statutory approach and a conceptual approach, with legal materials consisting of primary, secondary and tertiary legal materials which are analyzed qualitatively. The results of this research show that responsibility, as has been explained, is a state of being obliged to bear everything that occurs as a result of a mistake made by someone to another person due to their error or negligence. This also applies to carriers who collect fares not in accordance with the rules set by the government. , by observing several legal provisions in accordance with the laws that have been established, the carrier can be held responsible for acts of collecting fares that do not comply with the rules because the carrier is responsible for any losses experienced by passengers due to errors or negligence committed by the carrier. The legal protection that is obtained is usually an effort to provide a sense of security to passengers. In general, legal protection is realized in various forms, for example through providing compensation and so on. Any passenger who feels they have suffered a loss can sue the carrier.